Hubungan Dukungan Sosial dan Spiritual Penderita HIV/AIDS dengan Kualitas Hidup Penderita HIV/AIDS - Abdul Ghoni; khusnul khotima; Sri Astutik Andayani (STIKES Citra Delima Bangka Belitung, 2019)
According to Bare and Smeltzer, HIV/AIDS not only poses physical problems but also causes social and psychological problems. Social problems in people with HIV/AIDS in the form of stigma and discrimination from the surrounding environment. Know the relationship of social and spiritual support of people with HIV/AIDS with the quality of life of HIV/AIDS in the RSU Dr. H. Koesnadi District Bondowoso. This study uses observation correlation, with a Cross-Sectional approach whereby researchers use questionnaires to 43 respondents using the total sampling technique.This research is going for SPSS test Spearman Rank with significance value (Asymp. Sig) was obtained by the results of the prior and following conduct of 0.001 < 0.05, meaning Ho was rejected and Ha accepted. There is a relationship of social and spiritual support of people with HIV/AIDS with the quality of life of HIV/AIDS in the RSU Dr. H. Koesnadi District Bondowoso